Instructional Design for Meaningful Learning through Experience-Anchored Reflective Inquiry (EAR-I) - Febi Robianti (Indonesian Journal Publisher, 2025)
This study aims to conceptualize and articulate the Experience-Anchored Reflective Inquiry (EAR-I) model as a structured pedagogical framework that repositions experience as an epistemic–reflective anchor. Employing a conceptual–theoretical design and analytical synthesis, Qur’anic principles related to experience, tadabbur, epistemic humility, and knowledge-seeking were thematically interpreted, mapped onto pedagogical functions, and synthesized into an ordered instructional structure. The study yields two conceptual outcomes: a procedural design framework for translating Qur’anic epistemic principles into instructional logic and the EAR-I model consisting of five interrelated stages. The findings indicate that anchoring reflection in lived experience stabilizes inquiry and supports coherent meaning construction, offering a replicable framework for meaningful learning across diverse educational contexts.